St. Louis, Mo., Rev. Ordinances ch. 29, art. 11, § 3 (1881) - (:unkn) unknown (My University, 1881)
Prohibited carry of any sling, cross bow and arrow, air gun, or other contrivance for ejecting, discharging or throwing any fragment, bolt, arrow, pellet, or other missile of stone, metal, wood, or other substance capable of inflicting injury or annoyance in any street, alley, walk, or park of the city of Saint Louis.
Keywords: CARRY